Pengaruh Problem Based Learning Berbantuan Video Terhadap Kemampuan Berpikir Kritis Pada Materi Sistem Pencernaan Manusia Kelas VIII Smp Pahlawan Nasional - Monica Theresia; Ramlan Silaban (CV.ITTC INDONESIA, 2024)
The Effect of the Video-Assisted PBL Model on the Critical Thinking Ability of Class VIII Human Digestive System. Critical thinking is the ability to analyze, manage information, and design solutions to problems. The PBL model means that students can play an active role in solving the problems given. This research uses a research designpretest-posttest control group design. The research instrument used an objective essay test of critical thinking skills with 12 questionspre-test andpost-test. The research uses instrument validation tests, prerequisite tests, hypothesis tests, testsCohen’s. normality testpretest The control class obtained normal results with 0.015 > 0.05, while the experimental class obtained results of 0.075 > 0.05 and was declared normal. The homogeneous test was found to be 0.427 > 0.05, and was said to be homogeneous. Hypothesis testing resulted in an increase in students' critical thinking skills. As for the average valueexperimental class pretest 60 control class 50 while onposttes experimental class 87 control class 78 Meanwhile, testCohen's results were 1.16 in the medium category.